Larval anatomy of Andean tadpoles of Telmatobius (Anura: Ceratophryidae) from Northwestern Argentina - Candioti, M. Florencia Vera (Zootaxa, 2008)
In this paper I study the oral, buccopharyngeal, and musculoskeletal configuration in tadpoles of nine Telmatobius species from Northwestern Argentina (T. atacamensis, T. ceiorum, T. laticeps, T. oxycephalus, T. pinguiculus, T. pisanoi, T. cf. schreiteri, T. scrocchii, and T. stephani; N = 30, Gosner stages 31–36). Specimens were prepared according to standard clearing and staining protocols; additionally, I applied landmark and outline-based geometric morphometric methods in order to quantify shape variation in chondrocrania, hyobranchial skeletons, and suprarostral cartilages. Although preliminary, results show a marked morphological uniformity on the analyzed levels, and overlapping interspecific and intraspecific variation, which renders species discrimination difficult. Some distinctive traits for the genus are bicuspidate buccal spurs, peculiar arrangement of buccal roof and floor papillae, tetrapartite suprarostral, adrostral cartilages, a lateral slip of the m. subarcualis rectus II-IV invading branchial septum IV, and a characteristic pattern of muscles inserted on the diaphragm. The conservative larval internal morphology in this genus could be explained by a recent speciation and a development possibly characterized by the postmetamorphic appearance of specific features.En este trabajo estudio la morfología oral, bucofaríngea y musculoesquelética de larvas de nueve especies de Telmatobius del Noroeste argentino (T. atacamensis, T. ceiorum, T. laticeps, T. oxycephalus, T. pinguiculus, T. pisanoi, T. cf. schreiteri, T. scrocchii y T. stephani; N = 30, estadios de Gosner 31–36). Los especímenes se prepararon siguiendo protocolos clásicos de transparentación y coloración diferencial; adicionalmente, apliqué métodos de morfometría geométrica basada en landmarks y contornos para cuantificar la variación de formas en condrocráneos, esqueletos hiobranquiales y cartílagos suprarostrales. Aunque de carácter preliminar, los resultados muestran una notable uniformidad morfológica en los niveles analizados, y una variación intraespecífica que se superpone con la interespecífica, dificultando la distinción entre especies. Algunos rasgos distintivos del género son un par de espolones bucales bífidos, un arreglo particular de las papilas del techo y piso bucales, suprarostral tetrapartito, adrostrales, un haz del m. subarcualis rectus II-IV invadiendo el septo branquial IV, y un patrón aparentemente característico de los músculos insertos en el diafragma. La morfología larval interna conservadora en el género podría explicarse por una especiación reciente y un desarrollo posiblemente caracterizado por la aparición postmetamórfica de los rasgos específicos.